Penicillin Skin Testing: Potential Implications for Antimicrobial Stewardship. Issue 8 (26th May 2013) - Unger, Nathan R.; Gauthier, Timothy P.; Cheung, Linda W.
<x xml:space="preserve">Abstract</x> As the progression of multidrug‐resistant organisms and lack of novel antibiotics move us closer toward a potential postantibiotic era, it is paramount to preserve the longevity of current therapeutic agents. Moreover, novel interventions for antimicrobial stewardship programs are integral to combating antimicrobial resistance worldwide. One unique method that may decrease the use of second‐line antibiotics (e.g., fluoroquinolones, vancomycin) while facilitating access to a preferred β‐lactam regimen in numerous health care settings is a penicillin skin test. Provided that up to 10% of patients have a reported penicillin allergy, of whom ~10% have true IgE–mediated hypersensitivity, significant potential exists to utilize a penicillin skin test to safely identify those who may receive penicillin or a β‐lactam antibiotic. In this article, we provide information on the background, associated costs, currently available literature, pharmacists' role, antimicrobial stewardship implications, potential barriers, and misconceptions, as well as future directions associated with the penicillin skin test.